PENERAPAN MEDIA PEMBELAJARAN BERBASIS ETNOSAINS UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH IPAS PADA SISWA KELAS IV - Itu, Maria Alexandra; Soro, Viorentina Meo; Lawe, Yosefina Uge; Ferdinandus, Maria Suzana (Jurnal Ilmiah Mandalika Education (MADU), 2024)
Abstract : This study aims to implement and evaluate the effectiveness of the use of ethnoscience-based learning media in improving the skills of fourth grade students in solving science problems. The research method used is classroom action research (CAR). This study aims to improve students' ability in solving problems through the use of ethnoscience-based learning media. Data were collected through problem-solving ability tests, classroom observations, and interviews with students and teachers. Data analysis was carried out qualitatively by comparing student progress between cycles to evaluate the effectiveness of the media. The results showed a significant increase in students' problem- solving abilities after using ethnoscience-based media. In the first cycle, the average score of students' problem-solving tests was 62.6 with a passing rate of 35%. In the second cycle, there was an increase with an average score of 75.5 and a passing rate of 75%. The increase from the first cycle to the second cycle was 12.9%, with a significant increase in the passing rate of 40%. In conclusion, the use of ethnoscience-based learning media is effective in improving the skills of fourth grade students in science problems at SDK Kisanata